2004
DOI: 10.1111/j.1469-8137.2004.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric gene flow between traditional and hybrid rice varieties (Oryza sativa) indicated by nuclear simple sequence repeats and implications for germplasm conservation

Abstract: Summary• Mixed-planting of traditional and hybrid rice ( Oryza sativa ) varieties is an ecological approach for rice disease control and yield increase, in addition to its effective role in in situ conservation of traditional rice varieties. To estimate gene flow between traditional and hybrid rice varieties, an experiment involving Huangkenuo and Shanyou-63 was conducted to allow free gene flow by mixed-planting of the two varieties in different cultivation patterns.• A simple sequence repeat (SSR) marker RM1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
5
25
0
Order By: Relevance
“…Outcrossing occurred across the remaining locations from 0.1% to 3.2%. The average outcrossing frequency over all locations was 0.7%, a result similar to hybridization rates reported in previous outcrossing studies Gealy et al 2003;Messenguer et al, 2001;Rong et al, 2004;Song et al, 2004;Zhang et al, 2003). Outcrossing detected in 2004 plots was 4-fold higher than in 2003 that may be due in part to evaluation of additional Clearfield cultivars at different locations.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Outcrossing occurred across the remaining locations from 0.1% to 3.2%. The average outcrossing frequency over all locations was 0.7%, a result similar to hybridization rates reported in previous outcrossing studies Gealy et al 2003;Messenguer et al, 2001;Rong et al, 2004;Song et al, 2004;Zhang et al, 2003). Outcrossing detected in 2004 plots was 4-fold higher than in 2003 that may be due in part to evaluation of additional Clearfield cultivars at different locations.…”
Section: Resultssupporting
confidence: 83%
“…Frequency of hybridization between cultivated rice and weedy biotypes in small plot studies was reported to be markedly affected by different cultivars. Chen et al (2004) and Rong et al (2004) detected variable outcrossing rates between traditional and hybrid rice under different planting designs. Langevin et al (1990) found that the highest outcrossing rates occurred during overlap of flowering time between cultivated and weedy plants.…”
Section: Introductionmentioning
confidence: 97%
“…Isolation distances are also critical for the co-existence of GM and non-GM crops (Rong et al 2004;Messéan et al 2006). The latter report also provides a decision table to determine the isolation distances necessary to keep adventitious GM presence due to gene flow below a desired threshold, for different field sizes and wind orientations, as well as demonstrating how isolation distances can be reduced when combined with non-GM buffer strips of different widths and/or with flowering time lags.…”
Section: Gene Flowmentioning
confidence: 99%
“…Experiments in Italy showed that pollen-mediated gene flow from a transgenic, herbicide-resistant rice variety to adjacent plants of a nontransgenic counterpart was 0.05 to 0.53 percent (Messeguer et al 2001). Modern rice cultivars are often grown near older landraces (locally adapted varieties that were domesticated and improved by traditional farmers) in Asia, and hybridization rates between these two groups also appear to be very low (Rong et al 2004). These findings are consistent with the small distances that are recommended for isolating and maintaining the purity of cultivated rice grown in seed nurseries.…”
Section: Extent Of Pollen-mediated Gene Flowmentioning
confidence: 99%